Turning avatar into realistic human expression using linear and bilinear interpolations - Mohammad, Dzulkifli (3D Research Center, Kwangwoon University and Springer-Verlag Berlin Heidelberg., 2014)
The facial animation in term of 3D facial data has accurate research support of the laser scan and advance 3D tools for complex facial model production. However, the approach still lacks facial expression based on emotional condition. Though, facial skin colour is required to offers an effect of facial expression improvement, closely related to the human emotion. This paper presents innovative techniques for facial animation transformation using the facial skin colour based on linear interpolation and bilinear interpolation. The generated expressions are almost same to the genuine human expression and also enhance the facial expression of the virtual human.